CAES as a Way for Large-Scale Storage of Surplus Energy in Poland from Renewable Energy Sources - Krzysztof Polański (Energies)
The ongoing energy transformation and growing share of renewable energy sources (RES) in electricity production force the search for large-scale energy storage facilities as a possibility for storing electricity from RES because its production is not correlated with the current demand in the power grid. This article discusses the use of salt caverns as large-scale energy storage facilities, proposing a combination of the possibilities of storing energy in natural gas and energy stored in compressed air. Based on the selected potential area where such a storage facility could operate in Poland, the optimal operating parameters of storage caverns were estimated. Several possible cavern exploitation scenarios were analyzed to estimate the impact of the convergence phenomenon in salt caverns on the active storage volume over the long term of exploitation. The obtained results showed that even a high frequency of cavern exploitation cycles does not significantly affect the loss of its capacity due to the convergence phenomenon. The results confirmed the possibility of the effective use of this type of installation for storing surpluses from RES.